CHARACTERIZATION OF NEW SYNTHESIZED Fe2O3 NANOPARTICLES AND THEIR APPLICATION AS DETECTION SIGNAL AMPLIFIERS IN HERBICIDE BENTAZONE ELECTROANALYTICAL DETERMINATION - Jokić, Anja; Petković, Branka; Jevtić, Sonja; Vasić, Vesna; Laban, Bojana (Bulletin of Natural Sciences Research, 2019)
The iron oxide nanoparticles (Fe2O3 NPs) were synthesized from two different iron salts by solid-state synthesis method. The synthesized powder of Fe2O3 NPs is soluble in water, and the colloidal dispersion was characterized by TEM, FTIR, UV-Vis spectroscopy and zeta potential measurements. Obtained NPs are spherical in shape with narrow particle size distribution and an average diameter of 3 nm. Further, the possible application of Fe2O3 NPs was proposed, due to significant electroanalytical signal amplification in the determination of herbicide bentazone in natural river water.
Keywords: Iron oxide; Nanoparticles; Solid-state; Herbicide bentazone; Electroanalysis